Performance of Athletes With Visual Impairment in Track-and-Field Events at the Paralympic Games, From 1988 to 2016. (May 2022) - Marmeleira, José
Introduction: The Paralympic movement has grown considerably over the last decades, but few studies have analyzed the performance evolution of the best athletes with disabilities. This study examined the performance of athletes with visual impairments in track-and-field events over eight Paralympic Games (1988–2016).Method: Results in the Paralympic track-and-field events for athletes with visual impairments (and in the corresponding track-and-field Olympic events) were collected from official public websites.Results: Analysis showed that most performances at Paralympic track-and-field events increased linearly over the years, which finding contrasts with the general stagnation in Olympic events. The improvements from 1988 to 2016 in Paralympic sprinting, middle- and long-distance running, throwing, and long-jumping events were 4.0–16.3%, 3.2–16.2%, 23.0–54.2%, and 4.9–18.9%, respectively. Men had better performances than women in running, throwing, and jumping events. In general, sports classes with a less severe level of visual impairment achieved higher performance levels than those with a more severe level of visual impairment, especially men. The competition density of Paralympic track-and-field events showed modest improvements.Conclusions: This study provides evidence that the performance of track-and-field athletes with visual impairments have been improving persistently over the last eight Paralympic Games, confirming that Paralympic athletes are achieving high-level performances.Implications for Practitioners: This study will be helpful for coaches and athletes with visual impairments who are setting performance (and training) goals for the Paralympic Games and other international athletic events.